Fermentation Ability of Lactobacillus plantarum on the Infertile Egg at Different Incubation Time - A. Mangalisu; . Nahariah; W. Hatta (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2015)
The use of infertile egg can be offset by increasing the quality of product by fermentation to be a highly competitive commodity. Fermented yield can be used as functional food ingredients which are good for health, for facilitating absorption, and for extending the shelf life of the product. The purpose of this research was to determine the fermentation ability of Lactobacillus plantarum on the infertile egg at different incubation time. Infertile egg was broken and sterilized for 15 minutes and then fermented for 0, 2, and 4 days. Parameters measured in this research were the total count of L. plantarum, pH value, lactic acid content, and moisture content. Experimental data were analyzed using analysis of variance of completely randomized design. The results showed that total L. plantarum (Log10 CFU/ml) increased in line with the incubation time, i.e. 8.3, 9.31, 9.73, respectively for day 0, 2, and 4 of the incubation time. The pH decreased as incubation time increased, namely 7.05, 5.67, 5.36, respectively for day 0, 2, and 4. The value of lactic acid content for day 0, 2, and 4 of incubation period was 0.62%, 1.28%, 2.15%, respectively while the water content was 71.3%, 73.21%, and 74.94%, respectively. In conclusion, this research proved the existence of the fermentation ability of L. plantarumtowards the infertile egg which were indicated by the increase of the total count of L. plantarum, lactid acid content and moisture content, even though pH value decreased as the incubation period increased. The optimum time of the incubation period was 4 days.